A Grammar of Southern Min The Hui'an Dialect - Chen, Weirong (Sinitic Languages of China ;, 2020)
Southern Min (also known as Hokkien or Minnan) is a major branch of Chinese spoken mainly in Fujian and Taiwan, but also in Guangdong, Hainan and Hong Kong, as well as in many countries of Southeast Asia. Highly conservative in its linguistic profile, it is considered by many scholars to be a living language fossil due to the preservation of many archaic features that reflect its long-lasting history and culture. Yet to date there has been no comprehensive study of Southern Min using a typological framework, as the tendency is to base analyses on the model of Mandarin Chinese, the standard language. This grammar aims to present a systematic description of the Hui'an variety of Southern Min, mainly based on data collected via naturally occurring conversation. The volume includes four parts: nominal structure, predicate structure, clause structure and complex sentences, as well as a brief overview of phonology. It will have great appeal for heritage speakers, graduate students and scholars in both Chinese linguistics and typology.